Trade effects of direct and indirect carbon pricing policies - Antonia Kurz; Stela Rubínová (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
This study examines how policies affecting the cost of using fossil fuels in production influence comparative advantage in the industrial sector. Firstly, we use a fixed-effects gravity model to estimate the export capabilities that determine comparative advantage. Subsequently, using data on direct (carbon taxes, ETS permit prices) and indirect (fossil fuel excise taxes and subsidies) carbon pricing instruments for 45 economies from 2010 to 2018, we estimate that a 10% increase in carbon price is associated with a decline in export capability in the most carbon-intensive industry by 0.3% to 0.7%. We find empirical support for competitiveness spillovers to domestic downstream industries. Overall, changes in carbon pricing explain up to 1.2% of the variation in export capabilities over time. We illustrate the potential impact of fossil fuel subsidies removal by comparing independent action to global coordination, concluding that coordinated efforts can reduce the adverse effects on comparative advantage.
Keywords: F18; Q48; Q56; Q58; 330; Carbon Pricing; Fossil Fuel Subsidies; Fossil Fuel Taxes; Comparative Advantage; Competitiveness